2022
DOI: 10.3389/fonc.2022.836087
|View full text |Cite
|
Sign up to set email alerts
|

PDIA2 Bridges Endoplasmic Reticulum Stress and Metabolic Reprogramming During Malignant Transformation of Chronic Colitis

Abstract: BackgroundChronic inflammation contributes to approximately 20% of cancers; the underlying mechanisms are still elusive. Here, using an animal model of colitis to colon-cancerous transformation, we demonstrated that endoplasmic reticulum (ER) stress couples with metabolic reprogramming to promote a malignant transformation of chronic inflammation.MethodsThe animal model for chronic colitis to colon-cancerous transformation was established in C57BL/6N mice by azoxymethane (AOM) and dextran sodium sulfate (DSS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…A mouse model was established using AOM/DSS treatment to identify proteins related to colon cancer, as depicted in Figure 1 A and as previously described 8 . The total duration of the study was 15 weeks and two days, including one week of free feeding, 14 weeks for model development, and two days between capsule endoscopy and euthanasia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse model was established using AOM/DSS treatment to identify proteins related to colon cancer, as depicted in Figure 1 A and as previously described 8 . The total duration of the study was 15 weeks and two days, including one week of free feeding, 14 weeks for model development, and two days between capsule endoscopy and euthanasia.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with inflammatory bowel disease (IBD) have an increased risk of developing CRC [4,5]. To investigate the underlying mechanisms and potential biomarkers of colon cancer, researchers have developed animal models that induce tumor growth through inflammation by utilizing substances, such as azoxymethane (AOM) and dextran sulfate sodium (DSS) [6][7][8]. AOM, a well-established carcinogen, creates DNA adducts [9], whereas DSS serves as an inflammatory agent that damages the epithelial lining of the colon [10].…”
Section: Ivyspringmentioning
confidence: 99%
“…[40] PDIA2 plays a role in the folding of nascent proteins in the ER to regulate signaling. [41] PLA2G6 can mediate apoptosis and premature degeneration of dopaminergic neurons in the substantia nigra. [42,43] Meanwhile, ROC-AUC estimates indicated that the prognostic features exhibited by ERSGRS performed favorably.…”
Section: Discussionmentioning
confidence: 99%